2018
DOI: 10.3390/en11082150
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Multi-Timescale Coordinated Control Strategy for Stand-Alone Microgrid with Hybrid Energy Storage System

Abstract: Abstract:A scientific and effective coordinated control strategy is crucial to the safe and economic operation of a microgrid (MG). With the continuous improvement of the renewable energy source (RES) penetration rate in MG, the randomness and intermittency of its output lead to the increasing regulation pressure of the conventional controllable units, the increase of the operating risk of MG and the difficulty in improving the operational economy. To solve the mentioned problems and take advantage of hybrid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In recent years, many research studies on P2H2P systems have dealt with the energy management systems, controller functions, technical challenges of RESS components, and economic analysis. Studies such as Giorgio Caua et al 2014 [19], L. Valverde et al 2016 [20], Mauricio Higuita Cano 2017 [21] and Yanfeng Liu et al 2018 [11] examined the optimal scheduling of the RESS components to maximize the benefit of the RE and minimize the investment cost. These research studies have concluded that an energy management strategy is essential for the optimal utilisation of the P2H2P systems as well as the optimization of the RESS.…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, many research studies on P2H2P systems have dealt with the energy management systems, controller functions, technical challenges of RESS components, and economic analysis. Studies such as Giorgio Caua et al 2014 [19], L. Valverde et al 2016 [20], Mauricio Higuita Cano 2017 [21] and Yanfeng Liu et al 2018 [11] examined the optimal scheduling of the RESS components to maximize the benefit of the RE and minimize the investment cost. These research studies have concluded that an energy management strategy is essential for the optimal utilisation of the P2H2P systems as well as the optimization of the RESS.…”
Section: Previous Workmentioning
confidence: 99%
“…Renewable energy storage systems (RESS) play a crucial role in maximizing the RER contribution to the SAM energy balance. Such RESS solutions can be a hybrid combination of more than one technology working together in a synergistic way [7,21]. However, the classic trend is to use a conventional diesel generator (DG) as a backup or to meet the peak load in combination with RESS for the optimal energy system component sizing to minimize capital cost [16,17,[21][22][23][24].From the available researches, it is evident that SAM with a high percentage of RE penetration and hybrid RESS can be reliable, cost-effective and more sustainable compared to a 100% fossil-fuel-based SAM [25].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Significant work has been done on the power to hydrogen to the power system (P2H2P) by concentrating on the technical obstacles to pick adaptive energy storage systems such as charge/discharge time, size, cost, safety & management, and life cycle problems [17,31]. In order to optimize the RE's utility and to reduce investment costs, reference [32][33][34] evaluated the best schedule of RESS components. These investigations have revealed that an energy management strategy is important for the efficient use and optimization of P2H2P systems.…”
Section: Previous Workmentioning
confidence: 99%